Disposable E-Tongue for the assessment of water quality in fish tanks - Chang, Chew-Cheen; Bahruddin, Saad; Misni, Surif; Mohd Noor, Ahmad; Ali Yeon, Md Shakaff (Molecular Diversity Preservation International, 2009)
link to publisher's homepage at http://www.mdpi.com